A Snapshot of 40 Years in Early Childhood Education and Care through Oral Histories. Issue 4 (December 2013) - Theobald, Maryanne; Cobb-Moore, Charlotte; Irvine, Susan
THE YEAR 2012 MARKED 40 years since the introduction of the Child Care Act 1972 and the federal government introduced financial support for the provision of childcare services in Australia. Significant changes have occurred in social, political and theoretical contexts of early childhood education and care (ECEC) during this time. Bringing these to life, this paper investigates archival data of key changes in ECEC in association with oral histories of staff, parents and children associated with The Gowrie Qld during the years 1972–2012. With narrative analysis considered alongside historical information, two dominant issues emerge as integral to ECEC in the past, now and the future. These are: 1) what constitutes effective teaching and learning in the educational program; and 2) professional expectations in ECEC. Building an historical picture, this paper provides for critical reflection on the past to inform current and future practices.